Burden of death associated with SARS-CoV-2 infection during the pandemic in Flint, Michigan (MI), mortality trends over the 2-year period: impact of social and health inequities - Mariam Younas; Danielle Osterholzer; Carlos F. Ríos-Bedoya (Cambridge University Press, 2024)
Abstract Background: This cross-sectional study aims to determine the mortality trends in patients with SARS-CoV-2 infection during the pandemic in Flint, MI. Methods: Records from 1,663 consecutive adult patients (≥18 years of age) with confirmed SARS-CoV-2 infection, admitted and discharged from our facility from 03/2020 through 02/2022, were abstracted and analyzed. Multivariable logistic regression analysis was performed to examine the association between study explanatory variables (ie, sex, age, co-morbidities, etc.) and the primary study outcome (ie, mortality). Results: During the 2-year study period, the overall crude 90-day mortality rate was 16.1% (267/1663), being lowest in the period 5 (Table 1). Male sex, older age, certain co-morbidities, supplemental oxygenation use, and lack of immunization were associated with mortality. Therapeutics such as remdesivir and steroids were not associated with improved survival. Conclusion: Despite substantial changes in supportive care, management and circulating variants, SARS-CoV-2 carried a significant mortality risk. Vaccination coverage in this high-risk study sample was low, at only 12%. Public health efforts should be focused at overcoming the barriers to vaccine acceptance in this high-risk unique population.